2012
DOI: 10.1007/s00025-012-0285-3
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet Shrinkage on Paths for Denoising of Scattered Data

Abstract: Abstract. We propose a new algorithm for denoising of multivariate function values given at scattered points in R d . The method is based on the one-dimensional wavelet transform that is applied along suitably chosen path vectors at each transform level. The idea can be seen as a generalization of the relaxed easy path wavelet transform by Plonka (Multiscale Model Simul 7:1474-1496, 2009) to the case of multivariate scattered data. The choice of the path vectors is crucial for the success of the algorithm. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Algorithm 1 shows the easy-path procedure to find a path π in a region R: starting from some point (which for example can be chosen using the lexicographical ordering), the algorithm tries always to select the closest avaiable neighbour. If there are more points equally close, it selects the one that would make for the straightest path, the rationale being that a more regular path will lead to a smoother signal (see for example [7] for a proof that, when f is sufficiently…”
Section: Easy-pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Algorithm 1 shows the easy-path procedure to find a path π in a region R: starting from some point (which for example can be chosen using the lexicographical ordering), the algorithm tries always to select the closest avaiable neighbour. If there are more points equally close, it selects the one that would make for the straightest path, the rationale being that a more regular path will lead to a smoother signal (see for example [7] for a proof that, when f is sufficiently…”
Section: Easy-pathmentioning
confidence: 99%
“…In [15] and [14] it was shown that, with a suitable choiche of the paths, the N -term approximation given by the EPWT is optimal for piecewise-Hölder functions. In [16] the EPWT was used as part of a hybrid method for Image Approximation while in [7] for denoising of scattered data.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the EPWT is an adaptive transform in contrast to the other transforms mentioned above. Its approximation properties are well understood and its usefulness for image processing is well established, see [49,97,96].…”
Section: Shearletsmentioning
confidence: 99%
“…In Plonka et al (2012) and Plonka et al (2013) it was shown that, with a suitable choice of the paths, the N -term approximation given by the EPWT is optimal for piecewise-Hölder functions. In Plonka et al (2011) the EPWT was used as part of a hybrid method for Image Approximation while in Heinen and Plonka (2012) for denoising of scattered data.…”
Section: Rbepwtmentioning
confidence: 99%
“…append ψ to π v = ψ − p p = ψ remove ψ from Q end while 20: return π 3 The Region Based Easy Path Wavelet Transform rationale being that a more regular path will lead to a smoother signal (see for example Heinen and Plonka (2012) for a proof that, when f is sufficiently smooth, a straighter path gives smaller wavelet coefficients). This is done by computing the scalar product of the increment vector with a preferred direction vector, which at every iteration is updated to be the last increment in the path.…”
Section: Rbepwtmentioning
confidence: 99%